Recovering Hidden Texts: Palimpsests of the Matenadaran and their Disclosure - Jost Gippert (Mesrop Mashtots Institute of Ancient Manuscripts)
On the basis of four sample cases, the present article illustrates the prospects of the application of multispectral imaging to the study of palimpsests that are preserved in the Mesrop Mashtots Institute of Ancient Manuscripts (Matenadaran) in Yerevan. Taking into account the different physical structures of the samples, which comprise an isolated fragment (no. 647), two flyleaves (of manuscripts M2154 and M3938), and a fully palimpsested codex (manuscript M2130), it outlines the variety of Old Armenian materials in erkatʻagir script that were palimpsested, ranging from a colophon (M3938) via the History of Armenia by Movsēs Khorenatsʻi (M2154) and the Commentary on the Psalms by Theodoretus of Cyrrhus (Fragment no. 647) up to the treatise Against Heresies by Irenaeus of Lyon (M2130), and the insight into the history of the texts and the Armenian language that can be gained from these materials.
Keywords: Philology